Day 3 Wed, September 30, 2015 2015
DOI: 10.2118/175014-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Rock-Typing Index Based on Hydraulic and Electric Tortuosity Data for Multi-Scale Dynamic Characterization of Complex Carbonate Reservoirs

Abstract: Rock-pore-space geometry and network topology have a great impact on dynamic reservoir characteristics, in particular on capillary pressure and relative permeability curves. Hydraulic tortuosity is a key independent measurement relating the pore-space geometry and topology to the rock's effective porosity and absolute permeability. Therefore, hydraulic tortuosity can be an important concept for dynamic reservoir characterization and reservoir simulation. Our objectives are to recommend a new dynamic rock-typin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…This paper is a further development of the study presented by Ferreira et al (2015), where they have shown the importance of hydraulic tortuosity and corresponding pore-throat-size heterogeneity to the dynamic characterization of complex carbonate reservoirs. The main corresponding capillary effects are wettability; capillary pressure and relative permeability curves; end-point saturations; and hysteresis.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…This paper is a further development of the study presented by Ferreira et al (2015), where they have shown the importance of hydraulic tortuosity and corresponding pore-throat-size heterogeneity to the dynamic characterization of complex carbonate reservoirs. The main corresponding capillary effects are wettability; capillary pressure and relative permeability curves; end-point saturations; and hysteresis.…”
Section: Introductionmentioning
confidence: 79%
“…(2) Ferreira et al (2015) showed that RQI* has a much stronger correlation with pore-space geometry when compared with Winland R35, reservoir-quality (RQI) and flow-zone (FZI) indexes. Therefore, RQI* may significantly improve dynamic reservoir characterization, property population and upscaling of capillary effects for reservoir simulation of IOR / EOR in complex carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations